Implementasi Kurikulum Merdeka Dalam Penerapan Pembelajaran Berdiferensiasi di Lembaga PAUD - Meilina Durrotun Nafisa; Ruqqoyah Fitri (Universitas Cokroaminoto Palopo, 2023)
The Independent Curriculum is an educational approach that gives children the freedom to develop their potential based on individual interests, talents and needs. In implementing the independent curriculum, it certainly requires the role of the principal and teacher in order to create good teaching and learning activities for children. The purpose of this study was to explore and analyze (1) the preparation of differentiated teaching modules, (2) the implementation of differentiated learning, (3) the way teachers identify children's learning characteristics. This research model uses a qualitative case study approach with participatory observation methods and structured interviews. Data collection techniques were collected through direct observation or in-class observation, interviews with the principal and also two teachers in grades A and B, as well as documentation. The data analysis technique uses the Milles and Huberman models, namely data reduction, data presentation and data verification/drawing conclusions. The results of this study indicate that with the implementation of an independent curriculum, differentiated learning provides significant benefits for both children and teachers. In the context of the independent curriculum itself the teacher is given the freedom to arrange teaching modules and adjust to the implementation of differentiated learning according to learning strategies that suit the individual needs of each child. and in differentiated learning the teacher can identify the characteristics of learning in children and know the abilities, interests, and learning styles that will enable each child to grow and develop according to their potential